Constructing Academic Argumentation: The Role of Logical Connectives in Research Article Introductions - Indrawan, Fani; Hardinanto, Eko; Faizi, Ahmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to examine how logical connectives contribute to the construction of academic argumentation in research article introductions. It adopts a qualitative discourse-analytic approach supported by quantitative evidence, analyzing 15 research article introductions (13,221 words; 733 connectives). Connectives are classified based on their logical functions (ADD, CON, CAU, RES, SEQ, EXM) and mapped onto their argumentative functions (DEV, LIT, JUS, GAP). The findings indicate that additive connectives (ADD) are the most dominant, reflecting a tendency for writers to construct arguments through the accumulation and development of ideas, particularly in integrating previous studies. Contrastive connectives (CON) function not only to signal research gaps but also to establish the significance of the problem. Meanwhile, causal and resultative connectives contribute in strengthening the writer’s argument justification. Furthermore, sequential connectives organize the progression of argumentation. These findings suggest that logical connectives function as rhetorical resources that link micro-level linguistic features to macro-level of argumentative structures in the introductory section of research articles.